2011
DOI: 10.1111/j.1475-3588.2011.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation quality of whole‐school mental health promotion and students’ academic performance

Abstract: BackgroundThis paper argues for giving explicit attention to the quality of implementation of school-wide mental health promotions and examines the impact of implementation quality on academic performance in a major Australian mental health initiative.MethodHierarchical linear modelling was used to investigate change in standardised academic performance across the 2-year implementation of a mental health initiative in 96 Australian primary (or elementary) schools that was focused on improving student social-em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 27 publications
3
101
0
2
Order By: Relevance
“…43,44 Poor implementation has resulted in iatrogenic effects, including reactive disciplinary practices, multiple changes in programs implemented, inequitable outcomes for disadvantaged students, and consumer dissatisfaction and lack of confidence. 9,45 Given these consequences, education and mental health systems should consider using implementation science to more effectively integrate a full continuum of evidence-based mental health practices into schools. Sugai and Stephan 46 review key questions to consider when determining if and how to implement evidencebased mental health practices in schools: (1) Are need and intended outcome specified?…”
Section: Implementation Of Evidence-based Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…43,44 Poor implementation has resulted in iatrogenic effects, including reactive disciplinary practices, multiple changes in programs implemented, inequitable outcomes for disadvantaged students, and consumer dissatisfaction and lack of confidence. 9,45 Given these consequences, education and mental health systems should consider using implementation science to more effectively integrate a full continuum of evidence-based mental health practices into schools. Sugai and Stephan 46 review key questions to consider when determining if and how to implement evidencebased mental health practices in schools: (1) Are need and intended outcome specified?…”
Section: Implementation Of Evidence-based Practicesmentioning
confidence: 99%
“…In fact, data are mounting that it is in the best interest of schools and districts to provide such interventions to effectively promote students' academic success. 3,9 From a mental health perspective, one could not ask for a better opportunity to support the healthy social, emotional, and behavioral development of young children, and to identify and address mental health issues before or early after their onset. All mental health and school personnel could work together to support the healthy development of all students by strengthening protective factors, reduce the exacerbation of existing risk factors, and screen for conditions that might indicate development of later emotional, social, and mental health difficulties.…”
Section: Schools As An Implementation Opportunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Given the complexity of implementing mental health promotion school-wide, some schools do this more readily than others. For example, in Australia, significant positive relationships were found between the extent of implementation of a whole-school mental health initiative and students' differential mental health outcomes (Slee et al, 2009) and academic performance (Dix, Slee, Lawson, & Keeves, 2012). In order to assess implementation quality in the 96 schools studied, Dix, Slee, Lawson, and Keeves (2012) used latent class analysis to develop an 'implementation index'.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Australia, significant positive relationships were found between the extent of implementation of a whole-school mental health initiative and students' differential mental health outcomes (Slee et al, 2009) and academic performance (Dix, Slee, Lawson, & Keeves, 2012). In order to assess implementation quality in the 96 schools studied, Dix, Slee, Lawson, and Keeves (2012) used latent class analysis to develop an 'implementation index'. The index categorised schools as high, moderate, or low implementers of the mental health initiative based on a set of criteria (fidelity, dosage, quality of delivery) and found that high implementing schools showed greater academic gains than low implementing schools.…”
Section: Introductionmentioning
confidence: 99%